Emissions from a medium-duty crdi engine fuelled with diesel : biodiesel blends - Duda, Kamil; Wierzbicki, Sławomir; Mikulski, Maciej; Konieczny, Łukasz; Łazarz, Bogusław; Letuń-Łątka, Magdalena (Silesian University of Technology, 2021)
In the present work, biofuels produced from different raw fatty materials have been proposed as a dominant fuel component in biodiesel–diesel fuel blends. Biofuels were produced from pork lard and rapeseed oil by alkali transesterification using methyl alcohol. Blends of biofuels in volumetric proportions of 60 and 80% of the biocomponent and the remaining part of the conventional fuel were used in a compression ignition engine designed for medium-duty vehicles. The experiments were conducted at two engine rotational speeds (1500 and 3000 rpm, respectively) and a set of load conditions (50, 100, and 200 Nm, respectively). The tests focused on engine efficiency parameters (brake-specific fuel consumption and brake fuel conversion efficiency) as well as exhaust gas emissions (hydrocarbons, carbon monoxide, and carbon dioxide were determined). The obtained results indicate that blends containing biocomponents produced from pork lard were characterized by superior fuel consumption and efficiency results, compared to blends containing biocomponents produced from rapeseed oil. In terms of exhaust emissions, biocomponents produced from pork lard were also characterized by lower emission of all of the examined components compared to rapeseed methyl ester–diesel blends. This study proposes that fuel components obtained from custom (animal) raw-fatty material can be an effective substitute for commonly used rapeseed oil methyl esters.
Keywords: fuel blending; exhaust emissions; common-rail; engine efficiency; biodiesel; fi=Energiatekniikka|en=Energy Technology|